RANCANG BANGUN WEBSITE E-COMMERCE PADA CV. ANDIKA SAKTI - Felicia Sylviana; Dedy Jayadi (Universitas Palangka Raya, 2014)
CV. Andika Sakti is handicraft product shop. It sells various snacks produk. CV. Andika Sakti wasmarketing their product through conventional way where customers came directly to the shop to buy theproduct. It brought about some shortcomings such as the limitation of promotion coverage andconsequently their potential product was not really popular among market community. Other hindranceappears when it comes to the competition among other handicraft industry from small to high scaleenterprises. Therefore, the CV. Andika Sakti must have a different marketing strategy to be able tocompete and getting new more customers. A new system was needed to solve the problem, toaccommodate both the marketing strategy and selling process. One solution that could be done was bybuilding e-commerce web-based application.E-commerce website with web 2.0 at the CV. Andika Sakti consists of collaborated contents. Web2.0 is web technology which combines some of technologies commonly used in web building such asHTML, CSS, and Javascript. The methodology used for building the software was waterfall methodology.This method consists of some steps in building software. Those were analysis, design, coding, testing, andmaintenance. As a result, an e-commerce application was created which runs in web 2.0 to accommodatea series of marketing activity at the CV. Andika Sakti.CV Andika website developed using PHP programming, MySQL database server, and theXAMPP web server and tested with blackbox testing. The results of this testing, the customer can easilyplace an order, payment and get the product information without having to come to CV. This website alsofacilitates the CV to promote products with very affordable costs and expand marketing because in doingonline and simplify report generation of data items, ordering, and sales. On this website are suggested todevelop the design to make it more attractive appearance and facilitate online payment transactionsonline because now the website has been banned from using the forex / banking sites.